Acid and Base modified Pectin from Orange Peel as an Effective Bio-adsorbent for Pb(II) and Cr(VI) from Textile Industry Wastewater - Hanifa, Nur Lailatul; Afifah, Afifah; Wijaya, Destia Kusuma; Nurmazaya, Nufus; Qomariyah, Ani (Indonesian Journal of Chemical Research, 2023)
Modifying the methoxyl group on pectin from Siam orange peel (Citrus nobilis) has been done. Pectin was obtained from the peel of Siam orange by extraction method. The modified pectin obtained were analyzed using the FT-IR (Fourier Transform-Infra Red Spectroscopy) method, the XRD (X-Ray Diffractometry), and surface appearance images using SEM (Scanning Electron Microscopy). Pb(II) and Cr(VI) metals which can be adsorbed by the adsorbent then analyzed by UV-Visible Spectrophotometer. The results of the FT-IR analysis was found that the modification of the methoxyl group was successful. XRD analysis showed that the modified pectin adsorbent produced amorphous properties. The maximum pH for Pb(II) adsorption was obtained, namely pH = 6 and the maximum pH for Cr(VI) adsorption was pH =7. The best adsorption time variation for Pb(II) was 240 min and for Cr(VI) was 500 min. The best adsorbent for adsorption of Pb(II) was base-modified pectin adsorbent, while the best adsorbent for adsorption of Cr(VI) was base-modified pectin adsorbent. It could be proven that base-modified pectin was able to adsorb Pb(II) and acid-modified pectin was able to absorb Cr(VI) better (Pb(II) 80% adsorption percentage and 90% Cr(VI) adsorption percentage) than previous studies, namely pectin without modification (adsorption percentage obtained 60-70%).